Audio-Responsive Architectural Visualization: Linking Musical Features with Real-Time Digital Rendering (Architecture Image Studies, 2025)
The tendency in the visualization of architecture is better observed in the transformation of the architectural visualization as inert image to the multisensory and active digital mediation. Audio-responsive visualization is one of these new directions, providing a contentious conceptual base on which to reconsider the process of corporate translation of spatial perception, affect and environmental awareness into real-time architectural imagery. In this study, the researcher presents the concept of a hybrid conceptual-technical model that can be used to connect musical feature extraction and adaptive rendering rules so that the visual outputs can evolve continuously depending on the sonic features. At the crossroads of computational design, architectural representation, interactive media, and phenomenology, the paper outlines the theoretical basis as well as the system process by which sound-based visualization can be accomplished. The conceptual part investigates the role of rhythm, timbre, frequency, and amplitude in the formulation of spatial interpretation of the musical qualities that could be brought forth as generative stimulants in the architectural imaging logics. The technical part presents a prototype workflow described with short time fourier transforms (STFT), spectral centroid tracking, rhythmic onset detection and energy mapping to affect color dynamics, geometry deformation, particle behavior and environmental lighting. The hybrid paradigm is then understood through the representational agency, digital materiality and human perceptual agency. These findings imply that audio-responsive visualization extends the architectural visualization beyond traditional photorealism and still composition to produce images that are immersive, time-based and full of affect, and appeal to modern representational cultures. The research paper then provides a conclusion on the implications of the study to real-time rendering practice, design pedagogy, public installations, and future interdisciplinary research at the convergence of architecture, sound studies, and computational media.